Meningkatkan Kapasitas Kelompok Tani Sejati Melalui Manejemen Branding dan Strategi Pemasaran Digital Produk Pupuk Organik - Wanita, Titta; Herianto, Herianto; Ariyani, Gina; Pratama, Andika; Rizaldi, Muhammad; Endang Prasetyowati, Rini (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The conventional marketing system for agricultural products has not been able to increase sales of products produced by farmer groups. This community service activity intervention aims to empower the Sejati Farmers Group through the socialization of branding management and digital marketing strategies for organic fertilizer products. This activity was carried out in July 2024 at the Sejati Farmers Group, Lendang Nangka Utara Village, Masbagik District, East Lombok Regency, with 18 participants. The service method used participatory and personal communication. This training resulted in a 25% increase in knowledge and a 15% increase in organic fertilizer sales in the three months after the training. In addition, this activity provides alternative solutions to environmental and social problems, as well as improving the welfare of the local community.